PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) DALAM UPAYA MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SD NEGERI 123 PEKANBARU - Aliyah, Vijannatin; ', Zulkifli; ', Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on beginning observation author does, that is in batural sciences study stills teacher domination existence uses lecture method inclined boring, besides undercommunication will involve student activity in will do study activities should student can touch direct with things that activity that be done, so that result learns student balum increase. This watchfulness design class action watchfulness (PTK). This watchfulness is done at class vb country elementary school 123 pekanbaru school year 2014/2015. Subjek this watchfulness class student vb semester 2 school year 2014/2015 at country elementary school 123 pekanbaru with total 33 person. based on watchfulness result and pembahsan so inferential that study model applications numbered head together (nht) can increase result learn student. Result enhanced learns from score base to my cycle that is in first cycle is got ketuntasan as much as 15 students or 45% and in cycle ii 82% with enhanced as big as 21.46% membanding beginning score. This mean study model applications numbered head together (nht) can increase result learn student. the first meeting first cycle teacher activity enhanced is got average 69% with good category and in meeting 2 average activity that done student 81% with good category. While in meeting 2 activities that done teacher as big as 94% with category very good.Kata Kunci: numbered head together, hasil belajar siswa.